2016
DOI: 10.1055/s-0042-102653
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Maximal Lactate Steady State in Endurance Runners

Abstract: This study aimed to predict the velocity corresponding to the maximal lactate steady state (MLSSV) from non-invasive variables obtained during a maximal multistage running field test (modified University of Montreal Track Test, UMTT), and to determine whether a single constant velocity test (CVT), performed several days after the UMTT, could estimate the MLSSV. Within 4?5 weeks, 20 male runners performed: 1) a modified UMTT, and 2) several 30?min CVTs to determine MLSSV to a precision of 0.25?km?h?1. Maximal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
2
12
0
3
Order By: Relevance
“…Several 30 min constant workloads on a treadmill were performed to identify the highest workload (km·h –1 ) at which CBL increased >1 mMol·L –1 between the 10th and 30th min of exercise (Beneke, 2003 ). After 7 days from the second GXT EXP , all participants performed the first MLSS trial at the individual workload associated to their 85% of VT 2 , based on previous studies (Llodio et al, 2016 ; Pallarés et al, 2016 ). Depending on the results of the first MLSS - test, successive trials with a 48-h rest between sessions were increased or decreased 0.5 km·h –1 until MLSS criteria was fulfilled (Pallarés et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several 30 min constant workloads on a treadmill were performed to identify the highest workload (km·h –1 ) at which CBL increased >1 mMol·L –1 between the 10th and 30th min of exercise (Beneke, 2003 ). After 7 days from the second GXT EXP , all participants performed the first MLSS trial at the individual workload associated to their 85% of VT 2 , based on previous studies (Llodio et al, 2016 ; Pallarés et al, 2016 ). Depending on the results of the first MLSS - test, successive trials with a 48-h rest between sessions were increased or decreased 0.5 km·h –1 until MLSS criteria was fulfilled (Pallarés et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, methods identifying the relationship between submaximal constant velocity bouts and HR responses could be a simple and valid alternative [60] when controlling factors affecting HR monitoring, such as dehydration [61]. In addition, the combination of constant velocity and incremental tests in the field was also suggested to be valid in identifying the anaerobic threshold along with the MAS [62]. Of note, field running testing could be more difficult to apply due to the constraints associated with field and weather conditions.…”
Section: Training Monitoringmentioning
confidence: 99%
“…Analyzing the results, we can see that along with the study in question, there are studies in the literature with high correlations between the different methods of anaerobic threshold evaluation (de Lucas, Dittrich, Junior, de Souza, & Guglielmo, 2012;Fraga et al, 2014;Llodio, Gorostiaga, Garcia-Tabar, Granados, & Sánchez-Medina, 2016). In the recent study published by Guimaraes et al (Guimarães, Campos, de Souza, & da Silva, 2017), the authors found agreement between the methods of determination of anaerobic threshold velocity using blood lactate through the Dmax method and anaerobic threshold velocity using the heart rate deflection point.…”
Section: Discussionmentioning
confidence: 89%